Caring for Patients With Physical Disabilities: Assessment of an Innovative Spinal Cord Injury Session That Addresses an Educational Gap. (November 2019) - John, Janice Thomas; Block, Lauren; Stein, Adam; Vasile, Elizabeth; Barilla-LaBarca, Maria-Louise
Abstract : Abstract: Despite the fact that one fifth of Americans live with disability, caring for these patients is not routinely part of the undergraduate medical student curriculum. An innovative session addressing care of patients with spinal cord injury was developed for medical students and led by physiatrists, faculty experts in communications, and individuals with spinal cord injury. A mixed-method design was used in evaluating students' knowledge, skills, and attitudes following this curriculum. Quantitative evaluation was performed with a written essay question and checklist items from an objective structured clinical examination station. The session was given to 296 students from 2016 to 2018. On the objective structured clinical examination, 94% asked about sexual function, 85% asked about activities of daily living, 77% asked about instrumental activities of daily living, and 47% of students evaluated skin health. Students demonstrated respectful (99%) and nonjudgmental (99%) attitudes with spinal cord injury standardized patients and 91% interacted with the standardized patients caretaker appropriately. Themes emerged from the student survey including the following: the value of having real patients present during the session, exposure to physical medicine and rehabilitation as a specialty, and the advantage of a small group format. This session provided students with tools necessary to care for patients with spinal cord injury.